Comparison between Compression Strength of Composite Resin with and without Stamp Technique - Yusrini Pasril; Chantika Azzahra Anindita Putri (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2024)
Background: This study aims to determine whether there is a difference in compression strength between resin composites that use the stamp technique and those that do not use the stamp technique. Objective: To identify the effect of the stamp technique with occlusal matrix on the compression strength and compare it with the one without stamp technique. Materials and methods: This study used an occlusal matrix from a transparent impression made of silicone to print the occlusal teeth. This transparent impression was attached to the resin surface composite prior to polymerization and remained on the surface until polymerization ended. The advantage of using this transparent occlusal matrix is ​​that the light cure can penetrate through the transparent layer of the impression. It can be used to isolate oxygen during polymerization. Results: The average compression strength of composite resin with the stamp technique was 128.5300 ±17.23023 MPa, while composite resin without the stamp technique was 91.2460 ±8,72802 MPa. Conclusion: This study showed the difference between the two test groups, where the resin composite using the stamp strength had a higher compression strength.